Ferroberaunite, Fe2+Fe3+5(PO4)4(OH)5⋅6H2O, a mixed-valence iron member of the beraunite series, from the Gravel Hill mine, Perranzabuloe, Cornwall, England. (16th June 2022) - Tvrdý, Jaromír; Plášil, Jakub; Vrtiška, Luboš; Sejkora, Jiří; Škoda, Radek; Dolníček, Zdeněk; Petr, Martin; Veselovský, František
Abstract: The new mineral ferroberaunite, Fe 2+ Fe 3+ 5 (PO4 )4 (OH)5 ⋅6H2 O (IMA2021-36; symbol: Fbru ), occurs in cavities of 'limonite' iron ore from the Gravel Hill mine, Perranzabuloe, Cornwall, England. Its flattened prismatic crystals up to 400 μm long are dark green to olive green, transparent to translucent, with a vitreous lustre, pearly on cleavages. The Mohs hardness is ~3–4. The density measured by the flotation method is 2.94(2) g⋅cm –3, the calculated density is 2.907 g⋅cm –3 . Ferroberaunite is biaxial (–), with α = 1.736(2), β = 1.765(3), γ = 1.786(5) at 589 nm, 2Vmeas. = 68(3)°, 2Vcalc. = 79°; dispersion of optical axes is strong, r > v ; orientation is Y = b ; X ≈ a, Z ≈ c . Pleochroism is strong: X = bluish-green >> Z = green > Y = yellow. Electron-microprobe analyses gave the empirical formula (Fe 2+ 0.75 Ca0.01 Mn0.02 Fe 3+ 0.22 )Σ1.00 (Fe 3+ 4.88 Al0.04 )Σ4.92 (PO4 )4 O0.11 (OH)4.76 ⋅6H2 O. Ferroberaunite is monoclinic, C 2/ c, with a = 20.8708(3), b = 5.1590(8), c = 19.2263(3) Å, β = 93.3186(17)°, V = 2066.7(3) Å 3 and Z = 4. The eight strongest lines in the powder X-ray diffraction pattern are [ d meas, Å ( Irel., %) ( hkl )]: 10.410 (100) (200), 9.606 (14) (002), 7.271 (11) (20$\bar{2}$ ), 5.203 (4) (400), 3.467 (12) (600), 3.325 (6) (60$\bar{2}$ ), 3.201 (6) (006), 2.600 (4) (800). The mineral is isostructural with beraunite, redefined recently as Fe 3+ 6 (PO4 )4 O(OH)4 ⋅6H2 O.